Prevalence of Depression, Suicidal Ideation, Alcohol Intake and Nicotine Consumption in Rural Central India. The Central India Eye and Medical Study - Jost B. Jonas; Vinay Nangia; Marcella Rietschel; Torsten Paul; Prakash B. Behere; Songhomitra Panda‐Jonas (2014)
Background To investigate the prevalence of depression, suicidal ideations, alcohol and nicotine consumption in adults in an agrarian society mostly unchanged by the effects of urbanization. Methods The Central India Eye and Medical Study is a population-based study in rural Central India close to the tribal belt and included 4711 subjects (aged 30+ years). Depression was assessed by the Center for Epidemiologic Studies Depression Scale (CESD), suicidal ideation by six standardized questions, nicotine use by the Fagerstroem Nicotine Tolerance Questionnaire (FTNQ), and alcohol consumption by the Alcohol Use Disorders Identification Test (AUDIT). Results Mild to moderate depression (CESD sum score: 15–21) was detected in 1862 (39.6%) individuals (33.5% of men, 44.8 of women), and major depression (CESD sum score >21) in 613 (13.0%) individuals (8.1 of men, 17.3% of women). Suicide attempt was reported by 199 (4.2%) participants and suicidal thoughts during the last 6 months by 238 (5.1%) individuals. There were 887 (18.9%) smokers and smokeless tobacco was consumed by 1968 (41.8%) subjects. Alcohol consumption was reported by 1081 (23.0%) participants; 283 (6.0%) subjects had an AUDIT score ≥8 (hazardous drinking), and 108 (4.63%) subjects a score ≥13 (women) or ≥15 (men) (alcohol dependence). Conclusions In rural Central India, prevalence of major depression was comparable to figures reported from other developing countries. Prevalence of smoking and hazardous alcohol consumption was higher than as reported from urban regions. Measures should be taken to address the relatively high prevalence of suicide attempts and thoughts on suicide in rural Central India.